Negative Impacts of Pandemic Induced At-Home Remote Learning Can Be Mitigated by Parental Involvement - Guillaume, Mathieu; Toomarian, Elizabeth Y.; Van Rinsveld, Amandine; Baskin-Sommers, Arielle; Dick, Anthony Steven; Dowling, Gayathri J.; Gonzalez, Marybel Robledo; Hasak, Lindsey; Lisdahl, Krista M.; Marshall, Andrew T.; Nguyen, Quynh Trang H.; Pelham, William E.; et al. (Frontiers in Education, 2022)
Format changes in U.S. schooling in response to the COVID-19 pandemic varied by month and by school district, ranging from exclusively home-based to full in-person learning. The impact of these changes on adolescent schooling experiences, and the factors that mitigate such impact, have been challenging to quantify. To address these challenges we employed bi-monthly repeated surveys of youths (N = 6, 546, aged 13–14 years) in a longitudinal study, starting before the pandemic peak (October 2020) and continuing through one year after the pandemic was declared (March 2021). We investigated how school format (in-person vs. remote) impacted objective time spent on academic activities and the subjective experience of school, and how these were influenced by parental engagement. Periods of exclusive at-home remote schooling were pervasive—reported by more than 60% of youths—and linked to a reduction in school enjoyment and time spent on reading, math, and science. In contrast, such periods were linked to more time with parents or guardians helping with school activities, and the frequency of such parental involvement was associated with reductions in negative feelings about school. Results point to potential pathways to mitigate the negative consequences of future school disruptions.